Creative Economy-Based MSMEs Chips Development Model from Maqashid Sharia Perspective - Arsiah Dwi Cintana; Rahmat Daim Harahap; Purnama Ramadani Silalahi (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
The background of this research is driven by the importance of empowering MSMEs in improving a sustainable local economy, while ensuring that these economic activities are in accordance with sharia principles. This research aims to develop a creative economy-based chips MSME development model by considering the Maqashid Syariah perspective in Perlanaan Village, Simalungun. This type of research is using a qualitative approach with the PESTEL Analysis technique (Political, Economic, Social, Technological, Environmental, and Legal) which reveals that political stability, government support, economic conditions, social trends, technological advances, environmental awareness, and legal regulations play an important role in the success of chip MSMEs. The research sample will be purposively selected among the chip MSMEs operating in Perlanaan Village. Data will be collected through in-depth interviews, observation and analysis of relevant documents. The data will be thematically analyzed to identify the challenges and potentials of chip MSMEs in the context of the creative economy and Maqashid Syariah. The results of this research are expected to provide new insights in the development of sustainable chip MSMEs that fulfill sharia principles, and provide relevant policy recommendations. The implication of this research is its contribution in strengthening the base of a sustainable local creative economy and promoting the values of justice, balance, and economic sustainability based on Maqashid Sharia in the context of MSMEs in Indonesia, particularly in Perlanaan Village, Simalungun.Keywords: MSMEs; Creative Economy; Maqashid Syariah